Harvest Time has an Effect to the Quality of Red Dragon Fruits (Hylocereus polyrhizus (Weber) Britton & Rose) during Storage - Rosmaiti Rosmaiti (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2021)
TThe aim of this research is to know the influence of harvest time variety against the quality of red dragon fruits (Hylocereus polyrhizus (Weber) Britton & Rose) during storage. This research utilizes Complete Random Design (CRD) non factorial with three repetitious. The observed factor is harvest time factor of red dragon fruits (Hylocereus polyrhizus (Weber) Britton & Rose) which comprises of 30 HSA, 32 HSA, 34 HSA, 36 HSA and 38 HSA. The obtained data is analyzed by style examination analysis (ANOVA). If the treatment tangible impact so that it is continued by BNJ 0,05 test. The observed parameters are: fringe color and fruit skin, fruit succulence, fruit substance and fruit quality decrease. The research results indicate that after harvested, fringe color and the skin of red dragon fruits (Hylocereus polyrhizus (Weber) Britton & Rose) on all harvest time have hue color 5GY. As for value mark and chroma, after harvested and saved is different. The succulence of red dragon fruits (Hylocereus polyrhizus (Weber) Britton & Rose) harvest time 30 HSA is more succulent in comparison to the other harvest time after saved for 6 days. Harvest time 32 HSA has the highest fruit hardness level compared to other harvest times. The highest fruit weight loss was obtained at the 38 HSA harvesting age treatment. The color and taste of dragon fruit that the panelists liked the most was the harvest age of 32 HSA with the respective percentages of 46.67% and 53.33%.